A case study of service quality towards TM, MITC Melaka for year 2007 / Nurul Nazurah Mohamad Nasri - Mohamad Nasri, Nurul Nazurah (2009)
The purpose of this case study is to explain how the best ways of handling complaints (billings and payment, installation, and packages offered) can meet the service quality of TM Melaka. These studies are selected from well-known databases- such as “ScienceDirect”, “EBSCOhost” and “Emeraldinsight”. An observation is done to gather some data and some review of selected books of Service Management have been done through these studies. The paper identifies the gap between theories and what company has practiced to achieve those theories.